Hubungan Pengetahuan dan Sikap Ibu tentang Manfaat Imunisasi Lengkap pada Bayi Usia 0 – 9 Bulan di Puskesmas Teladan Medan - Dewi Sartika; Ketrin Bondar; Desilayani Putri Siringoringo (Universitas Malahayati Lampung, 2023)
ABSTRACT In 2022 the government will organize BIAN (National Childhood Immunization Month) in order to increase coverage of complete basic immunization in children. This was because during the Covid 19 pandemic there was a decrease in the coverage of complete basic immunization. Based on the latest routine data from the Indonesian Ministry of Health, coverage of complete basic immunization has decreased significantly since the start of the COVID-19 pandemic, from 84.2% in 2020 to 79.6% in 2021. Basic immunization is very important for infants aged 0-12 months to provide immunity from diseases that can be prevented by immunization (PD3I), including Tuberculosis, Diphtheria, Pertussis, Tetanus, Polio, Hepatitis B and Measles. The purpose of this study was to determine the relationship between knowledge and attitudes of mothers about the benefits of complete immunization in infants 0-9 months. This research was conducted at the Medan Exemplary Community Health Center in 2022 for 1 month starting from September 2022 and ending in October 2022. The research design was descriptive analytic using a cross-sectional design with a sample of 30 people. Based on the statistical test using chie-square, it shows a p-value = 0.006 or p 0.05, meaning that H0 is rejected and Ha is accepted, which means that there is a frequency distribution of mother's knowledge about the benefits of complete immunization in infants 0-9 months. For maternal attitudes, the chie-square results show a p-value = 0.004 or p 0.05, meaning that H0 is rejected and Ha is accepted, which means that there is a frequency distribution of maternal attitudes about the benefits of complete immunization in infants 0-9 months. In terms of knowledge and attitudes, the results of the chie-square show a p-value = 0.001 or p 0.05, meaning that Ho is rejected and Ha is accepted, which means that there is a relationship between knowledge and attitudes of mothers about the benefits of complete immunization in infants 0-9 months. The conclusion from the above research is that there is a relationship between knowledge and attitudes of mothers about the benefits of complete immunization in infants 0-9 months at the Medan Exemplary Public Health Center in 2023. It is expected that every mother who has a baby 0-9 months to bring the baby immunized from birth so that the baby gets complete immunization. Keywords: Knowledge, Attitude, Immunisation ABSTRAK Pada tahun 2022 pemerintah menyelenggarakan BIAN (Bulan Imunisasi Anak Nasional) dalam rangka meningkatkan cakupan imunisasi dasar lengkap pada anak. Hal ini disebabkan karena pada saat pandemi Covid 19 terjadi penurunan cakupan imunisasi dasar lengkap. Berdasarkan data rutin terbaru Kementerian Kesehatan RI cakupan imunisasi dasar lengkap telah menurun secara signifikan sejak awal pandemi covid 19, dari 84,2% pada tahun 2020 menjadi 79,6% pada tahun 2021. Imunisasi dasar sangat penting diberikan pada bayi berusia 0 – 12 bulan untuk memberikan kekebalan dari penyakit yang dapat dicegah dengan imunisasi (PD3I) antara lain Tuberkolosis, Difteri, Pertusis, Tetanus, Polio, Hepatitis B dan Campak. Tujuan penelitian ini untuk mengetahui Hubungan Pengetahuan dan Sikap Ibu tentang manfaat imunisasi lengkap pada bayi 0 – 9 bulan. Penelitian ini dilakukan di Puskesmas Teladan Medan Tahun 2022 selama 1 bulan mulai dari bulan September 2022 dan berakhir Oktober 2022. Desain penelitian ini analitik deskriptif menggunakan rancangan cross- sectional dengan sampel sebanyak 30 orang. Berdasarkan uji statistic menggunakan chie- square menunjukan nilai p-value = 0,006 atau p0,05 artinya H0 ditolak dan Ha diterima yang artinya ada distribusi frekuensi pengetahuan ibu tentang manfaat imunisasi lengkap pada bayi 0 – 9 bulan . Pada sikap ibu hasil chie-square menunjukan nilai p-value = 0,004 atau p0,05 artinya H0 di tolak dan Ha diterima yang artinya ada distribusi frekuensi sikap ibu tentang manfaat imunisasi lengkap pada bayi 0 – 9 bulan. Pada pengetahuan dan sikap hasil dari chie-square menunjukan nilai p-value = 0,001 atau p0,05 artinya Ho di tolak dan Ha diterima yang artinya ada hubungan pengetahuan dan sikap ibu tentang manfaat imunisasi lengkap pada bayi 0 – 9 bulan. Kesimpulan dari penelitian ini adalah ada hubungan pengetahuan dan sikap ibu tentang manfaat imunisasi lengkap pada bayi 0 – 9 bulan di Puseksmas Teladan Medan Tahun 2023. Diharapkan setiap ibu yang memiliki bayi 0 – 9 bulan untuk membawa bayi imunisasi sejak lahir sehingga bayi mendapatkan imunisasi lengkap. Kata Kunci: Pengetahuan, Sikap, Imunisasi